Reccurent trauma-induced aphthous stomatitis in adjustment disorder patients - Y. Yuliana; Saka Winias; Hening Tuti Hendarti; Bagus Soebadi (Dental Journal (Majalah Kedokteran Gigi), 2019)
Background: Adjustment disorder is a temporary psychological condition related to emotional responses or behaviour in reaction to stress resulting from certain changes in a specific period of an individual’s life yet which does not significantly affect his/her daily life. Recurrent aphthous stomatitis (RAS) constitutes recurrent inflammation of the oral mucosa, in the form of an ulcer, frequently associated with psychological stress. Occasionally, a patient does not realise that she/he is suffering from a psychological disorder until the emergence of clinical symptoms, among them recurrent ulcers the causes of which are unknown. Purpose: This article presents a case of adjustment disorder diagnosed from symptoms observable in the oral cavity. Case: The case involved a 21-year-old student who presented with the symptoms of large, painful ulcers on her tongue, the inside of her cheek, and the floor of her mouth. These symptoms had been observable for one month but remained untreated. The patient only ate once a day or even once every two days. An introverted personality, she did not associate with other people. Case management: The procedure covered anamnesis, clinical examination, blood laboratory tests, total immunoglobulin E (IgE), an Antinuclear Antibody (ANA) test, bacterial and fungal culture in ulcus, questionnaire screening on psychological disorders, cortisol level examination and referral to a psychiatrist. Symptomatic therapy administered to the patient led to recovery of the ulcer in 29 days. Conclusion: RAS can be triggered by psychological stress which induces changes in the immune system and oral mucosa tissue.